Developing Social Competence Among Dyslexics - Garg, Geeta (JOURNAL OF INDIAN EDUCATION, 2010)
Dyslexia, the most prevailing learning disability, refers to reading difficulties. With so much emphasis on interventions for such children to be competitive in the academic world, we lose sight about what really prepares a child to be happy, confident, and secure in the real world. The dyslexics regularly face many challenges, and require interventions besides numeracy and literacy skills. For such children, social competence is the most important aspect to be taken care of. Because of their consistent academic under achievement, they face peer rejection and ignorance. Exclusion from a normal peer group can deprive rejected children of opportunities to develop adaptive social behaviours. They have higher risks of developing patterns of aggressive behaviour, mental and emotional traumas. The social competence deficits, if left untreated, may increase over time, along with feelings of social anxiety and inadequacy. Therefore, it is of great importance to make such children socially competent. An early intervention and support at key moments can change their world. The present article attempts to give measures of developing social competence among dyslexics to make them feel confident and contributing members of this social world.